Determining the indicators of social capital theory to social network sites - Sander, Tom; Teh, Phoey Lee * (2014)
The authors theoretical research provided a framework to define and measure social capital in social network sites. This paper determining with a qualitative method the theoretical dimensions of this framework. The result of this paper is the explanation of social capital theory in social network sites under the consideration of the identified indicators. The sample for this case is students, and the research needs further confirmation by other samples and methods. But this paper gives a first interesting insight in social network sites explained with the social capital theory and provides a first guidance for further research projects.